(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The reports used in education’s field to identify and assess the behavior of students, and reports used in the security field to pursue criminals or terrorists in the community, lack some of the criteria that help the conversion of these reports to information that can be used before the terrorists commit the criminal event. This is called "early to predication of terrorist and criminal behavior" of persons. This early predication of mentioned behavior is the main idea of our work, because there are projects to find the terrorists or criminals after doing the criminal events. These projects identify and analyze the data from the occurred even, including some information about the area and the persons. This is the major difference between these projects, and our work in this article. إن التقارير المستخدمة في المجال التربوي لتحديد وتقييم سلوك الطلاب والتقارير المستخدمة في المجال الاجتماعي الأمني لملاحقة الأفراد الاجراميين في المجتمع تفتقد إلى بعض المعايير التي تساعد وتساهم في تحويل هذه التقارير إلى بيانات يمكن الاستفادة منها ليس فقط بعد حدوث الحدث الاجرامي او الارهابي بل قبل حدوثه وهذا ما ندعوه التنبؤ المبكر عن السلوك الاجرامي والارهابي للأشخاص. هذا التنبؤ المبكر عن السلوك المذكور هو فكرة العمل الرئيسية لأنه توجد أعمال في هذا المجال ولكن لإيجاد الافراد الذين قاموا بعمل اجرامي وذلك بتحليل البيانات الناتجة عن العمل الإجرامي وهذا هو الفرق الرئيسي بين هذه الاعمال والعمل الذي قمنا به والمراد ايضاح فكرته في هذا المقال.